The leading role of MYC in DNA damage response: exploring opportunities for therapeutic inhibition - Giuntini, Fabio; Whitfield, Jonathan R.; Massó-Vallés, Daniel; Soucek, Laura (Frontiers in Cell and Developmental Biology, 2026)
MYC performs a dual role in DNA Damage Response (DDR), promoting genomic instability through replication stress, R-loop formation, and topoisomerase-mediated damage, while simultaneously activating DNA repair pathways to maintain cell survival. This review provides a comprehensive analysis of how MYC inhibition affects DDR pathway dependencies. In fact, when MYC is inhibited, cancer cells lose both their proficient DNA repair capacity and their protective mechanisms against replication stress. This creates a therapeutic window in which combining MYC inhibitors with DDR-targeting agents may achieve synergistic anti-cancer effects. Central to this approach is the exploration of rational combination strategies that pair MYC inhibitors with various DDR modulators including Poly (ADP-ribose) polymerase (PARP) inhibitors, ATR/CHK1 inhibitors, and other DNA repair pathway disruptors. This review summarizes preclinical evidence demonstrating enhanced therapeutic efficacy when MYC inhibition is combined with DDR-targeting agents and discusses early clinical findings that support this promising therapeutic strategy.